The Language of Smart Cities - Uttara Purandare (South Asia Multidisciplinary Academic Journal)
This paper uses discourse analysis methods to get a better understanding of India’s Smart Cities Mission which was launched in 2015. It focuses on nine policy documents and assessment frameworks published by the nodal ministry at federal level to guide 100 smart cities. The paper situates the Mission within the global smart city rhetoric and within the rhetorical shifts toward a softer version, smart city 2.0. The paper examines whether the Indian Mission follows a similar trajectory or whether it has persisted with the techno-utopian, economic driven, and citizen-blind version of the smart city paradigm. Studying the discourse and imagery of these documents, it brings to light the fact that, while the language has changed and become more inclusive, the interventions recommended by the Ministry have become more data dependent and technologically driven. The paper presents the reasons for which discourse analysis is a useful method for studying smart cities, and offers a basis on which more detailed city-level analyses can be undertaken in the Indian smart city context.